KONSEP RISIKO BISNIS DALAM ISLAM DAN RELEVANSINYA BAGI PRAKTIK MUDARABAH PADA LEMBAGA KEUANGAN SYARIAH - Nurohman, Dede (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
This paper aims to build the concept of business risk in an Islamic perspective by making the mudarabah financing product as a starting point for the development of the theory. This research includes library research. The method of collecting data is documentation, collecting relevant library sources both in print and electronic form. The library sources were analyzed through Content Analysis with the stages of data reduction, data presentation, and taking conclusions or verification. The results of the research indicate that the concept of risk that has been understood and practiced in Islamic business and financial institutions is oriented only to the materialism value. It is not in accordance with the spirit of Islamic economics. Islam views risk not only on the aspect of material gain and loss, but more importantly, Islam prioritizes the value of maslahah. Therefore, mudarabah which is considered a product that contains a high risk, for the Islamic economy, the risk inherent in mudarabah is an opportunity to achieve the ideal goal, namely the creation of benefit in the form of increasing the welfare of the poor, in accordance with the noble values ​​contained in the mudarabah itself. The results provide an initial framework for the development of Islamic risk management discipline.